Kinetics of the Reaction of Pyrogallol Red, a Polyphenolic Dye, with Nitrous Acid: Role of •No and •No2 - Lissi-Gervaso, E; Rubio-Campos, M (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
In the present work we studied the reaction under gastric conditions of pyrogallol red (PGR), a polyphenolic dye, with nitrous acid (HONO). PGR has been used as a model polyphenol due to its strong UV-visible absorption and its high reactivity towards reactive species (radicals and non-radicals, RS). The reaction was followed by UV-visible spectroscopy and high performance liquid chromatography (HPLC). A clear decrease of the PGR absorbance at 465 nm was observed, evidencing an efficient bleaching of PGR by HONO. In the initial stages of the reaction, each HONO molecule nearly consumed 2.6 PGR molecules while, at long reaction times, ca. 7.0 dye molecules were consumed per each reacted HONO. This result is interpreted in terms of HONO recycling. During the PGR-HONO reaction, nitric oxide was generated in the micromolar range. In addition, the rate of PGR consumption induced by HONO was almost totally abated by argon bubbling, emphasising the role that critical volatile intermediates, such as •NO and/or nitrogen dioxide (•NO2), play in the bleaching of this phenolic compound.